Do Variations in State Mandatory Child Abuse and Neglect Report Laws affect Report Rates among Medical Personnel? - Faulkner, Amanda Ellen (2009)
Each state and territory within the United States is required by the Child Abuse Prevention and Treatment Act [42 U.S.C. 5101 et seq.] to maintain a mandatory suspected child abuse and neglect reporting law, requiring certain professionals who regularly see children to report any suspicions of child maltreatment to child protective services. It is well documented that mandatory reporters fail to report each case of suspected child maltreatment they witness. This study sought to determine whether differences in three specific variables within the mandatory report laws had an effect on the frequency with which medical personnel report suspected child abuse and neglect. The three variables analyzed were: definitional scope of emotional abuse; standard of knowledge required for a report; and severity of penalty imposed on those who knowingly fail to report cases of child abuse and neglect. Data was obtained from the Child Maltreatment 2006 annual report printed by the Health and Human Services Administration of Children, Youth and Families. Of the three variables assessed, only severity of penalty yielded a significant association with report rate. States with lower report rates were significantly more likely to have lenient penalties for failure to report compared with those who had report rates above the national average (O.R. = 5.0, 95% C.I. = 1.165-21.465). It is recommended that states consider increasing the severity of the sanctions enforced for failure to report suspected child abuse and neglect. Although standard of knowledge requirements were not significantly associated with report rates, the literature suggests that standardization of this portion of the mandatory report laws could improve report rates, particularly among physicians